Health utilities in Chinese patients with coronary heart disease and impaired glucose tolerance (ACE): A longitudinal analysis of a randomized, double‐blind, placebo‐controlled trial. Issue 7 (25th July 2022) - Leal, José; Becker, Frauke; Lim, Lee‐Ling; Holman, Rury R.; Gray, Alastair M.
Abstract: Background: We estimate health‐related quality of life and the impact of four cardiovascular events (myocardial infarction [MI], stroke, congestive heart failure, angina) and gastrointestinal events in 6522 Chinese patients with coronary heart disease (CHD) and impaired glucose tolerance (IGT) participating in the Acarbose Cardiovascular Evaluation (ACE) trial. Methods: Health‐related quality of life was captured using the EuroQol‐5 Dimension‐3 Level (EQ‐5D‐3L), with data collected at baseline and throughout the trial. Multilevel mixed‐effects linear regression with random effects estimated health‐related quality of life over time, capturing variation between hospital sites and individuals, and a fixed‐effects linear model estimated the impact of cardiovascular and gastrointestinal events. Results: Patients were followed for a median of 5 years (interquartile range 3.4‐6.0). The average baseline EQ‐5D score of 0.930 (SD 0.104) remained relatively unchanged over the trial period with no evidence of statistically significant differences in EQ‐5D score between randomized treatment groups. The largest decrement in the year of an event was estimated for stroke (−0.107, P < .001), followed by heart failure (−0.039, P = .022), MI (−0.021, P = .047), angina (−0.012, P = .047), and gastrointestinal events (−0.005, P = .430). MI and stroke reduced health‐related quality of life beyond the year in which the event occurred (−0.031, P = .006, and −0.067, P < .001, respectively). Conclusions: Acarbose treatment had no impact on health‐related quality of life in ACE trial participants with CHD and IGT. Events such as MI, stroke, heart failure, and angina reduce health‐related quality of life around the time they occurred, but only MI and stroke impacted on longer‐term health‐related quality of life. Abstract : Highlights The Acarbose Cardiovascular Evaluation (ACE) trial assessed the effects of acarbose in patients with coronary heart disease (CHD) and impaired glucose tolerance (IGT) in China. Acarbose treatment did not impact on health‐related quality of life in ACE trial participants with CHD and IGT. Myocardial infarction (MI), stroke, heart failure, and angina were found to reduce health‐related quality of life around the time they occurred; only MI and stroke may impact on longer‐term health‐related quality of life. 摘要: 背景: 我们评估了参加阿卡波糖心血管评估(ACE)试验的6, 522名中国冠心病(CHD)和糖耐量异常(IGT)患者的健康相关生活质量，以及四种心血管事件(心肌梗死(MI)、中风、充血性心力衰竭、心绞痛)和胃肠道事件的影响。 方法: 使用EuroQol‐5 Dimension‐3 Level(EQ‐5D‐3L)获取与健康相关的生活质量信息，收集基线和整个试验过程中的数据。运用具有随机效应的多水平混合效应线性回归估计随时间进展的与健康相关的生活质量，并记录医院和个人之间的差异，使用固定效应线性模型估计心血管和胃肠道事件的影响。 结果: 患者平均随访5年(四分位差3.4 6.0)。在试验期间，平均基线EQ‐5D得分为0.930(SD 0.104)保持相对不变，没有证据表明随机治疗组之间的EQ‐5D得分在统计学上有显著差异。在事件发生的一年中，使健康相关的生活质量下降幅度最大的是中风(‐0.107，p<0.001)，其次是心力衰竭(‐0.039，p=0.022)、心肌梗塞(‐0.021，p=0.047)、心绞痛(‐0.012，p=0.047)和胃肠道事件(‐0.005，p=0.430)。心肌梗死和中风降低了事件发生后一年与健康相关的生活质量(分别为0.031，p=0.006和‐0.067，p<0.001)。 结论: 阿卡波糖治疗对患有冠心病和糖耐量异常的ACE试验参与者的健康相关生活质量没有影响。心肌梗死、中风、心力衰竭和心绞痛等事件在发生时会降低与健康相关的生活质量，但只有心肌梗死和中风会对长期的健康相关生活质量产生影响。